Comparative CBCT analysis of the changes in buccal bone morphology after corticotomy and micro-osteoperforations assisted orthodontic treatment – Case series with a split mouth design - Anshuka A. Agrawal; Abhay P. Kolte; Rajashri A. Kolte; Varsha Vaswani; Usha Shenoy; Prachi Rathi (Saudi Dental Journal)
Purpose: Procedures such as Periodontally Accelerated Osteogenic Orthodontics (PAOO) support the use of osteotomy to aid tooth movement and rapid distraction of the periodontal ligament by utilizing tissue engineering principles with periodontal regenerative surgery. The aim of this study was to evaluate and compare the amount of tooth movement and the associated changes in buccal bone morphology between corticotomy and flapless Micro-Osteoperforation (MOP) assisted orthodontic treatment. Material and methods: A total of ten healthy patients between 18 and 25 years of age requiring orthodontic treatment were recruited for this clinical trial with a split mouth design. After orthodontic and periodontal examinations, Cone Beam Computed Tomography scans (CBCT) were done pre- (T1) and post- (T2) operatively for each patient to evaluate radiographic parameters such as buccal bone thickness, root resorption and dehiscence. Amount of tooth movement was also evaluated and compared. Results: The canine-premolar distance, measured in a time interval of 3 months and over a follow-up period of 6 months, reduced significantly from T1 to T2 at both corticotomy and MOP sites. At the corticotomy site, there was a mean increase in bone thickness of 1.15 ± 0.3 mm at coronal region, 0.48 ± 0.1 mm at mid-root region and 0.15 ± 0.0 mm at apical region. This increase in bone thickness was statistically significant at coronal level (p = 0.001) and mid-root level (p = 0.02). Significant increase in bone thickness was observed at MOP site. While on intergroup comparison, the difference was statistically significant at coronal level (p = 0.01). Conclusion: Both the techniques cause an increase in canine retraction in short period of time with almost no harm to periodontal structures. MOP being a flapless procedure allow clinicians to deliver an efficient orthodontic care. Keywords: Tooth movement, Cone beam computed tomography, Orthodontics